Investigating Supercritical Bended Flow Using Physical Model and CFD - Hamza Souli; Jihane Ahattab; Ali Agoumi (Modelling and Simulation in Engineering)
The flow in the bend channel used as spillway chute is complex due to the turbulence, the presence of shock waves, and vibrations. These transverse waves can damage the hydraulic structure. Our aim in this paper is to investigate the distribution of water surface in five curved channels with five relative curvatures ρ, different bottom slopes (1%, 2%, 10%, and 18%) and three different cross-sections. The objective is to give a solution to reduce the height difference between the inner and the outer walls. To achieve this goal, we used physical models to investigate the flow patterns, explore critical zones, and test several solutions to have a better performance. The reliability and accuracy of the numerical results were validated using the physical modelling for each case tested. Moreover, a comparison between the measured data, theoretical calculations, and numerical outcomes was done, to find a fitting law between the maximum wave height and the bend number. Furthermore, an optimal position of the guide wall was identified in real project of a spillway. The results of the physical model and numerical simulation show a good agreement; thus, the numerical model can play a crucial role in order to study hydraulic parameters, pressure, and velocity field and find solutions for hydraulic problems that occur in these structures.